Pengaruh Penambahan Persentase Kolostrum Sapi pada Kefir yerhadap Sifat Organoleptik (Aroma, Rasa, Tekstur dan Overall) - Astuti, Cahyaning Dwi; Setyawardani, Triana; Widayaka, Kusuma (ANGON: Journal of Animal Science and Technology, 2019)
Background. The objective of this reserch was to determine the effect of adding colostrum on kefir with different percentages of organoleptic properties. Material and methods. This study used a randomized block design (RBD) method using 1700 ml cow milk, 300 ml cow colostrum, and 40 g kefir seeds into 4 treatments tested by 25 semi-trained panelists. The treatment applied was the difference in cow colostrum namely K1 = 0% cow colostrum, K2 = 10% cow colostrum, K3 = 20% cow colostrum, K4 = 30% cow colostrum.The parameters observed were organoleptic properties of aroma, taste, texture and overall. The study was conducted on January 1-2, 2019 at the Laboratory of Animal Product Technology, General Soedirman University Faculty of Animal Husbandry. Results. The results showed that the addition of cow colostrum to kefir had no significant effect (P > 0.05) on aroma, had a significant effect (P< 0.05) on taste, texture and overall. The highest average is ranked 1 for the results of a typical kefir aroma with a value of 0.17, slightly sour taste with a value of 0.21, thick texture with a value of 0.42, and overall very like with a value of 0.29. Conclusion. The conclusion is that the addition of 30% cow colostrum can increase the taste slightly acidic, the texture is thicker and is preferred overall (overall), but can only increase the distinctive aroma of kefir in addition to cow colostrum 20%.